Analysis of frequencies of 21 autosomic microsatellite loci in populations of the cities of kiev, odessa, kharkov, dnipro and western ukraine - Savelieva, Maryna; Rushkovsky, Stanislav (ScienceRise: Biological Science, 2019)
Autosomal STR-loci are currently the most used tool in forensic genetics. The allele frequencies of STR loci are used to calculate the probability of random coincidence of DNA profiles for identifying individuals and to calculate likelihood of kinship. The aim of the research was to investigate the polymorphism of 21 criminally significant STR-loci in mixed populations of Kiev, Odessa, Kharkov, Dnipro and Western Ukraine. Materials and methods. The reference sample consists of 1200 unrelated persons. Genomic DNA was isolated from buccal epithelial cells using a ChelexR100 ion exchange resin. The isolated DNA was typed using the polymerase chain reaction method at the 21 autosomal loci that make up the GlobalFiler™ Express PCR Amplification Kit. PCR products were electrophoretically fractionated using the SeqStudio™ Genetic Analyzer System. Allele sizes were analyzed using GeneMapper 6 software. The allele frequencies were compared between populations. Results. Population genetic data for 21 STR loci were included in the GlobalFiler™ Express system (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, vWA, TPOX, D18S51, D5S818, FGA, D2S4433, D19S4231, 1919 , D10S1248, D1S1656, D2S1338, D12S391). The expected and observed heterozygosity, matching probability, power or discrimination, power of exclusion, polymorphic information content were calculated. The correspondence of the observed distribution of genotypes of Hardy-Weinberg equilibrium was determined. Findings. High informativeness of the studied individualizing system of 21 autosomal STR loci was shown. SE33 locus was first analyzed, which turned out to be the most hypervariable. Differences in the frequencies of alleles of STR loci between populations were noted